2018
DOI: 10.1007/s00300-018-2362-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification on thermal tolerance and acid–base regulation of Mytilus edulis from the White Sea

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag GmbH Germany, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…The combined impacts of OA and OW have been addressed with contrasting responses, such that the effects of OA and OW are either exacerbated (e.g., Di Santo 2015;D'Amario et al, 2020;Zittier et al 2018;Rodolfo-Metalpa et al, 2011) or ameliorated (e.g., Kroeker et al 2014;Knights et al, 2020;García et al, 2015;Jiang et al, 2018) in the presence of the other stressor (). Meta-analyses have suggested that the combined impacts of OA and OW on species physiology are especially devastating for the larval stages of many species (Przeslawski et al, 2015;Kroeker et al, 2013), presenting a major bottleneck for population persistence under changing oceanic conditions (Przeslawski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The combined impacts of OA and OW have been addressed with contrasting responses, such that the effects of OA and OW are either exacerbated (e.g., Di Santo 2015;D'Amario et al, 2020;Zittier et al 2018;Rodolfo-Metalpa et al, 2011) or ameliorated (e.g., Kroeker et al 2014;Knights et al, 2020;García et al, 2015;Jiang et al, 2018) in the presence of the other stressor (). Meta-analyses have suggested that the combined impacts of OA and OW on species physiology are especially devastating for the larval stages of many species (Przeslawski et al, 2015;Kroeker et al, 2013), presenting a major bottleneck for population persistence under changing oceanic conditions (Przeslawski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%